Освіта і кластерний вектор інноваційного розвитку - Пономарьов, Олександр Семенович (НТУ "ХПІ", 2010)
Основной чертой постиндустриального общества стал инновационный характер развития. Системную разработку и использование инноваций как фактор конкурентоспособности обеспечивают кластеры. В их деятельности важную роль играет система образования. Она формирует для них кадровое обеспечение и получает стимул собственного инновационного развития.

The basic line of postindustrial society was become by innovative character of development. System forming and use of innovations as a factor of competitiveness is provided by clusters. In their activity an important role is played by the system of education. It forms for them the skilled providing and gets the stimulus of own innovative development.
Еducationand cluster vector innovative development
Keywords: соціально-економічний розвиток; модернізація; бізнес; переваги; кадровий потенціал; конкурентоспроможність